La mobilité révélée par GPS - Benoit Feildel (Netcom)
A growing number of research on mobility, especially in the French speaking-world, is interested in Global Positionning System tools. When GPS tracks are most of the time used for statistical measuremt of travels, on our part, we have used GPS for a different purpose. Drawing on a map, built with the data collected during a travel survey with few inhabitants, we have used GPS track as a tool enabling the consciousness of a geographical living that is ordinary very difficult to reach. Doing so, we were able to ask people to think about the meaning of their own mobilities.